Taxation, uncertainty, and the cost of equity for a multinational firm - Diderik Lund (University of Oslo, Department of Economics, 2001)
From a CAPM-type model the cost of equity is derived for a firm operating under various foreign tax systems. The firm's shares are traded in a market which is unaffected by these systems. The cost of capital depends on the foreign tax system, even for fully equity financed projects. This is neglected in much of the literature. For a corporate income tax the main factor which reduces the cost of equity is the depreciation deductions. Compared with a neutral cash flow tax, this reduces the cost of equity because it acts as a loan from the firm to the government.
Keywords: G31; H25; 330; Cost of equity; taxation; weighted average cost of capital; uncertainty; Kapitalkosten; Kapitalertrag; Steuersystem; Multinationales Unternehmen; Capital Asset Pricing Model; Theorie